True to Life. British realist painting in the 1920s & 1930s. - Elliott, Patrick; Elliott, Patrick (Edinburgh : Trustees of the National Galleries of Scotland, 2017)
Frampton, meredith, Brockhurst, Gerard Leslie ; Gunn, Herbert James ; Philpot, Glyn ; Williamson, Harold ; Barker, Margaret ; Knight, Laura ; Hynes, Gladys ; Myles Glasson, Lancelot
True to Life: British Realist Painting in the 1920s and 1930s, Scottish National Gallery of Modern Art, Edinburgh, 1 juli tot 29 oktober 2017
boek